2015
DOI: 10.1038/tp.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipidomics analysis finds long chain cholesteryl esters to be associated with Alzheimer’s disease

Abstract: There is an urgent need for the identification of Alzheimer's disease (AD) biomarkers. Studies have now suggested the promising use of associations with blood metabolites as functional intermediate phenotypes in biomedical and pharmaceutical research. The aim of this study was to use lipidomics to identify a battery of plasma metabolite molecules that could predict AD patients from controls. We performed a comprehensive untargeted lipidomic analysis, using ultra-performance liquid chromatography/mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 36 publications
6
98
0
1
Order By: Relevance
“…The prediction of clinical symptoms of AD has employed imaging methods [2] to detect early structural changes and has identified changes in levels of tau and amyloid-beta (Aβ) in cerebrospinal fluid [3] and lipidomic profile in blood [4, 5] with only limited success. Cognitive testing offers an alternative, non-invasive, possibility for the prediction of AD: it can be performed easily and safely in a community setting, usually with little or no need for specialist equipment or particular technical skills.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of clinical symptoms of AD has employed imaging methods [2] to detect early structural changes and has identified changes in levels of tau and amyloid-beta (Aβ) in cerebrospinal fluid [3] and lipidomic profile in blood [4, 5] with only limited success. Cognitive testing offers an alternative, non-invasive, possibility for the prediction of AD: it can be performed easily and safely in a community setting, usually with little or no need for specialist equipment or particular technical skills.…”
Section: Introductionmentioning
confidence: 99%
“…These roles include the formation of lipid rafts, maintenance of membrane structure, and involvement in the onset, development, and resolution of inflammatory processes. Several genetic and cell biological studies have associated lipid metabolism with AD pathogenesis . Studies on brain tissue metabolomics supported this relationship and reported interesting changes in many lipid compounds, such as sphingolipids, lysobisphosphatidic acids, sphingomyelins, and desmosterols, in the brains of AD patients .…”
Section: Metabolomics In Ad Researchmentioning
confidence: 86%
“…Studies on brain tissue metabolomics supported this relationship and reported interesting changes in many lipid compounds, such as sphingolipids, lysobisphosphatidic acids, sphingomyelins, and desmosterols, in the brains of AD patients . Recently, six long‐chain cholesteryl esters (ChEs) were identified as potential biomarkers for AD using UPLC‐Q‐TOF‐MS and a random forest classifier, which were used to analyze plasma samples from 35 AD patients, 48 individuals with MCI, and 40 elderly controls . The identified ChEs were ChE 32:0, ChE 34:0, ChE 34:6, ChE 32:4, ChE 33:6, and ChE 40:4.…”
Section: Metabolomics In Ad Researchmentioning
confidence: 99%
“…Other plasma lipids classes reported to have close relationships with AD included bile acids (Greenberg et al, 2009), LysoPCs and (Trushina et al, 2013b) AD(n = 3) FTD(n = 4) LBD(n = 3) CN(n = 9) Serum CE-MS ↑b-alanine, creatinine, hydroxyproline, glutamine, isocitrate, cytidine (Tsuruoka et al, 2013) AD(n = 12) CN(n = 5) Whole brain MRS ↓N-acetyl-aspartate, g-aminobutyric acid; ↑ glutamate (Klunk et al, 1992) AD ( Changes in levels of uracil, xanthine, uridine, tyrosyl-serine, methylsalsolinol, nonanoylglycine, dopamine-quinone, caproic acid, vanylglycol, histidine, pipecolic acid, hydroxyphophinylpiruvate, creatinine, taurine, C16-sphingosine-1-phosphate, tryptophan, 5 0 -methylthioadenosine (Ibanez et al, 2013) phytosphingosine (sphingolipid precursors) (Li et al, 2010b), among others (Mapstone et al, 2014). Utilizing in-vial dual extraction protocol Godzien et al, 2013), abnormal levels of long chain cholesteryl esters/triglycerides (Proitsi et al, 2015;Proitsi et al, 2017) and omega-3 containing PC molecules (Whiley et al, 2014;Kim et al, 2016) have been shown in two separate study cohorts. Additionally, increased plasma levels of phosphorylethanolamine (PE) and PC species have been found to associate with brain amyloid burden (Voyle et al, 2016).…”
Section: Bloodmentioning
confidence: 99%